2020
DOI: 10.2196/19150
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile- and Web-Based Health Intervention Program for Diabetes and Prediabetes Self-Management (BetaMe/Melon): Process Evaluation Following a Randomized Controlled Trial

Abstract: Background Technology-assisted self-management programs are increasingly recommended to patients with long-term conditions such as diabetes. However, there are a number of personal and external factors that affect patients’ abilities to engage with and effectively utilize such programs. A randomized controlled trial of a multi-modal online program for diabetes self-management (BetaMe/Melon) was conducted in a primary care setting, and a process evaluation was completed at the end of the study perio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Moreover, mobile medical services of online hospitals are different from other mobile health care support applications. In their initial stage of promotion and operation, we should pay attention to the public’s expectations of, and willingness to use, these services [ 15 , 16 ]. Through the extension and application of the UTAUT model, we aim to determine the factors influencing willingness to use these services and the relationship between them; our research will fill this gap in the field of mobile medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mobile medical services of online hospitals are different from other mobile health care support applications. In their initial stage of promotion and operation, we should pay attention to the public’s expectations of, and willingness to use, these services [ 15 , 16 ]. Through the extension and application of the UTAUT model, we aim to determine the factors influencing willingness to use these services and the relationship between them; our research will fill this gap in the field of mobile medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Connected devices are dramatically changing many aspects in health care [4][5][6][7]. While in cardiology, the majority of devices are intended to monitor heart rhythm, others have a therapeutic purpose [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Given that higher engagement in mHealth interventions is usually associated with better outcomes [22,24,118], we propose that the samples in future studies should be more balanced with regard to gender and implement gender-sensitive feasibility and usability testing. Overall, the compliance with the app (90/109, 82.6%) and satisfaction with the app (86/100, 86%) were high and comparable with those of other mHealth interventions [99][100][101]119]. The usability of the app was rated with 71% (5.0/7.0 points) satisfaction.…”
Section: Comparison With Prior Workmentioning
confidence: 63%
“…The compliance with the app was satisfactory (90/109, 82.6%) and comparable with other studies. Signal et al [ 99 ] developed an eHealth intervention for prediabetes and diabetes self-management. They reported that 74% of the participants were actively engaged (ie, any use data were detected at any time throughout the 16-week intervention).…”
Section: Discussionmentioning
confidence: 99%